2017
DOI: 10.3892/ol.2017.5658
|View full text |Cite
|
Sign up to set email alerts
|

Anti-apoptotic protein Lifeguard does not act as a tumor marker in breast cancer

Abstract: The aim of the present study was to use an enzyme-linked immunosorbent assay (ELISA) to determine the concentrations of Lifeguard (LFG) protein in the serum of 36 patients diagnosed with breast cancer and to compare these values with the concentrations of LFG protein in the serum of 7 healthy volunteers in order to detect a possible association between the expression of LFG in the serum and the degree of malignancy of the disease. Although there is no direct association between the LFG protein concentration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…For example, it is assumed that the anti-apoptotic protein Lifeguard (LFG, a membrane-bound protein) is increasingly expressed via activation of the Pi3-K/Akt signal cascade and, thus, plays a decisive role in the inhibition of programmed cell death [ 25 , 26 ]. In this case, Bucan et al showed that combinational therapy consisting of chemotherapeutic downregulation of the Pi3-K/Akt pathway together with a preceding siRNA treatment to minimize the LFG expression level in MCF-7 breast cancer cells led to a cumulative apoptotic outcome with a significantly suppressed cell proliferation and survival [ 18 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is assumed that the anti-apoptotic protein Lifeguard (LFG, a membrane-bound protein) is increasingly expressed via activation of the Pi3-K/Akt signal cascade and, thus, plays a decisive role in the inhibition of programmed cell death [ 25 , 26 ]. In this case, Bucan et al showed that combinational therapy consisting of chemotherapeutic downregulation of the Pi3-K/Akt pathway together with a preceding siRNA treatment to minimize the LFG expression level in MCF-7 breast cancer cells led to a cumulative apoptotic outcome with a significantly suppressed cell proliferation and survival [ 18 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%